THE DEVELOPMENT OF PROFESSIONAL SUBJECTIVE POSITION OF MANAGEMENT HUMAN RESOURCES FOR HEALTH - Ol'ga L. Zadvornaya; V. Alekseevich Alekseev; Konstantin N. Borisov (Модернизация, инновация, развитие, 2016)
The article is devoted to the problem of development of professional-subjective position of managerial staff of health care in the system of continuous professional education in the conditions of optimization of activities of the health system. Professional and subject position reflects the position of individual managers in a professional environment, its relationship to the quality of professional activity, to himself, to patients and colleagues to level their skills.Purpose/objectives: analysis of core competencies, forming the professional and subject position of heads of medical organizations; identify possible ways of development of professional-subjective position of managerial staff of the public health based on the use of modern technologies and active methods of training in system of continuous professional education. Methodology. In conducting the present study used data from official sources, literature review, scientific methods of analysis and synthesis, comparative analysis and modeling. The results of the study indicate the necessity of actualization of the subject position of heads of medical organizations. Conclusions /Significance. The necessity of formation and development of professional subjective position of the heads due to the needs of society and the health care system with modern requirements for quality management training of health. Professional and subject position is a characteristic feature of a highly qualified specialist in the area of governance, reflecting its active attitude toward self and professional activity, factor of efficiency of activity of medical organizations. The real practice of activity of medical organizations requires improved approaches in the preparation of healthcare managers. Most of the leaders are having difficulties, associated not only with necessity of development of universal and professional competences, but also the necessity of development of professional-subjective position, professionally important personal qualities, personal interest in self-development and improvement. Despite the large number of scientific papers in the fi eld of managerial activities, a broad educational possibilities of managerial staff of health care in the system of continuous professional education, the problem of formation and development of professional and subject position of health care managers remains relevant and requires further development. The development of the leader as a personality, a subject of professional activity, formation of an active professional position is the most important task of the system of continuous professional education of managerial staff of health requires improved organizational, technological and methodological support of the educational process, adequate methods and training technologies, assessment of level of readiness of the expert to implement a professional-subjective position in terms of professional practice.